1987
DOI: 10.1002/maco.19870381003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold work on the oxidation behavior and carburization resistance of Alloy 800

Abstract: The structure of the oxide layer formed on Alloy 800 at 600°C in superheated steam markedly indicates the role of the grain boundaries as easy diffusion paths of Cr and Mn to the alloytoxide interface. Increasing the number of grain boundaries by lo-%% cold work leads to increasing Cr-and Mn-content in the scale and to decreasing oxide growth rates. Variation of the grain size by different annealing treatments leadssince the Cr-content in the scale is decreasing with the grain sizeto a linear relation of growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…A common high-Cr alloy (such as 18Cr-8Ni stainless steel) forms an inner layer of Fe/Ni oxide, during initial stages of oxidation, which eventually converts into a protective oxide, i.e., Cr 2 O 3 when sufficient Cr diffuses from the alloy bulk to the oxide scale-alloy interface. [202] The kinetics of transition of Fe/Ni oxide into protective layer of Cr 2 O 3 depends on the supply of chromium by diffusion in the alloy matrix, which is governed profoundly by grain size of the alloy. As clearly demonstrated in the literature, [203] a relatively fine grain (~17 lm or less) 18Cr alloy easily developed a uniform layer of Cr 2 O 3 .…”
Section: B Alumina Forming Nanocrystalline Alloys/coatingsmentioning
confidence: 99%
“…A common high-Cr alloy (such as 18Cr-8Ni stainless steel) forms an inner layer of Fe/Ni oxide, during initial stages of oxidation, which eventually converts into a protective oxide, i.e., Cr 2 O 3 when sufficient Cr diffuses from the alloy bulk to the oxide scale-alloy interface. [202] The kinetics of transition of Fe/Ni oxide into protective layer of Cr 2 O 3 depends on the supply of chromium by diffusion in the alloy matrix, which is governed profoundly by grain size of the alloy. As clearly demonstrated in the literature, [203] a relatively fine grain (~17 lm or less) 18Cr alloy easily developed a uniform layer of Cr 2 O 3 .…”
Section: B Alumina Forming Nanocrystalline Alloys/coatingsmentioning
confidence: 99%
“…Cr, Mn, Fe spinels are known to be protective in particular, if they are rich in Cr and Mn [23,24]. In the present case, this oxide formed on the lateral surfaces of the crack/void could have been further enriched with Cr by diffusion from the substrate.…”
Section: µM µMmentioning
confidence: 74%
“…It was established in the literature that a fine grain (~17 µm or less) stainless steel easily developed a uniform layer of Cr 2 O 3 . For an alloy with grain sizes greater than ~40 µm, this protective layer of Cr 2 O 3 was difficult to form due to insufficient grain boundary diffusion and inadequate chromium supply [98][99][100]. In nanocrystalline materials where grain size is very fine and diffusion coefficients are high, such Cr oxide formation should be facilitated by a large extent.…”
Section: Enhanced Diffusivity and Oxidation Resistancementioning
confidence: 99%
“…They reported that the oxide film nucleated at the grain boundaries needs to grow laterally for the formation of a uniform oxide layer and reported that the finer the grain size, the better the uniformity of oxide should be. Later it was shown that above a critical grain size, formation of a uniform Cr layer was not possible which could be understood based on the combined role of diffusion and nucleation site densities in the alloys [44,45,[98][99][100]. However, these studies were performed on the material where minimum grain size was a few microns.…”
Section: Nucleation Sites and Lateral Growth Of Passive Filmmentioning
confidence: 99%